PENERAPAN PROBLEM BASED LEARNING PADA MATERI KEGIATAN EKONOMI MATA PELAJARAN IPAS UNTUK KELAS IV SDN 4 AIR KUMBANG - Qudsiyah, Laelatul; Fahriza Fuadiah, Nyiayu; Murjainah, Murjainah (SCHOLASTICA JOURNAL JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2025)
This research was conducted with the aim of finding out the application of problem based learning in economic activity material in the science and science subject for class IV SDN 4 Air Kumban. In this application research, researchers used qualitative methode. Data collection techniques in this research were obtained from the result of interviews, observasions and test. The result of the research show that it can be implemented well. The application of problem based learning to economic activity material in the social science subject for class IV can foster enjoyable learning and student activity result increase by 90% in the verry good category because in its application students leam while working in groups and exchanging ideas together with their friends which makes learning possible more fun, collaborative and effective. And after implementing problem based learning, student learning outcomes experienced an increase 90% from the previous 20% in the economic activity material of the science and technology subject for class IV SDN 4 Air Kumbang. Keywords: Problem based learning, student activities, economic activity material.